Testing active learning workshops for reducing implicit stereotyping of Hispanics by majority and minority group medical students - Stone, Jeff; Moskowitz, Gordon B; Zestcott, Colin A; Wolsiefer, Katherine J (Stigma and health (Washington, D.C.), 2020)
The present research tested if having first year medical students complete active learning workshops would reduce their implicit stereotyping of Hispanics as medically noncompliant. The workshops were tested with 78-majority (White) group, 16-target minority (Hispanic, African-American and American-Indian) group, and 42-non-target minority (Asian-American and foreign born students from East Asia and Southeast Asia) group students in the 2018 and 2021 classes in the American Southwest. Prior to the workshops, students completed an implicit association test (IAT), and then participated in two workshops that covered the psychology of intergroup bias, the role of implicit bias in patient care, and activities for learning six strategies for controlling the implicit stereotyping of patients. The results showed that before the workshops, the level of implicit stereotyping of Hispanics was significant for the majority and non-target minority group students, but it was not significant for the target minority group students. After the workshops, target minority students again showed no bias, and implicit stereotyping was significantly lower for the majority group students, but not for the non-target minority students. The results suggest that the workshops may have been effective for majority group and target minority group students, but that more cultural tailoring of the materials and activities may be necessary to address implicit bias among some minority group medical students.